Creative strategies for school problems : solutions for psychologists and teachers - Durrant, Michael (A Norton professional book, 1995)
This book seeks to offer some ideas about how to deal with the [academic and behavioral problems] that teachers face daily. It rests on ideas developed in the field of brief therapy. Brief therapy is an approach that seeks to find ways to cooperate rather than confront. I begin with some thoughts about the role of theory and assumptions in counseling and therapy. Building on the discussion of theory, the book seeks to present practical strategies for dealing with the kinds of problems that school psychologists [and teachers] face, and I have tried to illustrate the various ideas with examples from my own work and from the work of others. The strategies aim to be practical and simple--however, that does not always mean they will be easy.